Data for: Tasting accents: Three studies on the influence of regional accents on people's expectation and perception of food - Baptista, Iuri; Swahn, Johan (Örebro University, 2026)
This dataset contains 20 audio files and raw data from three studies about the effect of accents on the expectations and perceptions of food. The audio files are small descriptions of the food stimuli recorded by a dialect specialist in four different accents from four Swedish counties (Skåne, Värmland, Stockholm, and Norrland) chosen to represent, respectively, the south, west, east, and north of the country. Study 1 contains data on 302 consumers’ liking of a vegan cream cheese and jam sandwich after they heard a description of the sandwich in the four mentioned accents. It also shows the willingness to meet (WTM) and a check-all-that-apply (CATA) description of the person telling a short story in the four different accents. Study 2 contains data on 314 consumers’ liking and CATA description of one dried pork sausage and one dried vegan sausage after hearing descriptions in two different accents (northern and southern). Study 3 contains data on 314 consumers’ willingness to try (WTT) and CATA description of four regional dishes after seeing a picture and listening to a description of them in the four different accents. All data was collected through online questionnaires hosted on EyeQuestion between February and Juni of 2025.

Denna datauppsättning innehåller 20 ljudfiler och rådata från tre studier om accenters effekt på förväntningar på och uppfattningar om mat. Ljudfilerna är små beskrivningar av matstimuli inspelade av en dialektspecialist i fyra olika dialekter från fyra svenska län (Skåne, Värmland, Stockholm och Norrland) valda för att representera södra, västra, östra och norra delen av landet. Studie 1 innehåller data om 302 konsumenters gillande av en vegansk smörgås med färskost och sylt efter att de hört en beskrivning av smörgåsen i de fyra dialekter. Den visar också villigheten att möta (WTM) och en "check-all-that-apply" (CATA) beskrivning av personen som berättar en novell i de fyra olika dialekter. Studie 2 innehåller data om 314 konsumenters gillande och CATA beskrivning av en fläsk ölkorv och en vegansk ölkorv efter att ha hört beskrivningar i två olika dialekter (norrländska och skånska). Studie 3 innehåller data om 314 konsumenters villighet att prova (WTT) och CATA beskrivning av fyra regionala rätter efter att ha sett en bild och lyssnat på en beskrivning av dem i de fyra olika dialekterna. All data samlades in via online-enkäter som publicerades på EyeQuestion mellan februari och juni 2025.
Data för: Tasting accents: Three studies on the influence of regional accents on people's expectation and perception of food
Keywords: consumer behaviour; konsumentbeteende; sensory evaluation; sensorisk bedömning; vegetarian dishes; vegetariska rätter; restaurant workers; restaurangarbetare; restaurant sector (lines of business); restaurangbranschen; accent (linguistics); accent; food services; matservice; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; OTHER; ÖVRIGT